Thermohydrodynamic modelling of journal bearings under varying load angle and negative groove flow rate - Brito, F. P. (2014)
The performance of hydrodynamic journal bearings is affected by the conditions under which the lubricant is fed to the bearing gap. Axial grooves are often used and, depending on their location relatively to the load line, they might substantially interfere with the hydrodynamic pressure generation and the thermal behaviour of the bearing. However, many of the existing tools for predicting bearing performance are not able to suitably predict bearing behaviour under varying load angle given the oversimplified way under which they treat lubricant feeding conditions. The present work proposes a detailed Thermohydrodynamic approach which realistically incorporates these conditions into the bearing analysis. Special care is put on the mass and energy-conserving models of the ruptured film region and on a detailed treatment of lubricant mixing within the vicinity of grooves. This includes the first full modelling of the effect of negative flow rate in a groove, a phenomenon originally described experimentally in detail by the authors in previous publications, and which happens for a broad range of load/groove angles. An extensive investigation on the influence of loading direction on the performance of twin groove journal bearings has been performed. This parameter is found to affect deeply all major performance parameters due to the interference of groove regions in the hydrodynamic pressure generation and in the flow rates at each groove.